The moon and the horse tamer: literary symbols and social divisions in the nationalist poetry of Cassiano Ricardo and Leopoldo Marechal - Moreira, Luiza Franco (Literatura e Sociedade, 1999)
Making use of Walter Benjamin's words, this essay has the purpose of showing that the best nationalist poems by Cassiano Ricardo e Leopoldo Marechal deserve to be treated as documents of civilization as well. The readings of "Full Moon" and "To the Horse Tamer Celedonio Barral" had the purpose of drawing attention to how much and what those texts reveal.